ACTIVE READING STRATEGIES (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article explores the conceptual framework and practical applications of core active reading strategies. We will define and examine proven techniques such as previewing, annotating, questioning (e.g., the SQ3R method), summarizing, and making textual connections. Furthermore, the discussion will be grounded in the cognitive science of learning, explaining how these strategies combat the limitations of working memory and leverage schema theory to enhance long-term knowledge integration. The necessity for explicit instruction in these strategies transcends academic disciplines. Whether a student grappling with complex primary sources, a professional synthesizing market analyses, or a citizen evaluating news media, active reading skills are indispensable for critical thinking, informed decision-making, and lifelong learning. This paper argues that moving beyond literacy to strategic competency in reading is not merely an educational enhancement but a fundamental requirement for navigating the complexities of the modern information landscape.